(untitled) (KULT_online, 2010)
The connection between such different areas as the natural sciences and literature requires a high level of interdisciplinarity. Andrea Pelmter’s monograph links the two by establishing the concept of experiment as a common item of reference for the discourse of science and literature and by analysing its importance for the works of the Austrian writer Robert Musil. Unfortunately, the genuine literary quality of the work is lost from view. Nevertheless, Pelmter’s dissertation can be recommended to not just Musil readers, but to all those interested in the problematic of knowledge in literature, and who have a certain understanding of the methodological difficulties of such an interdisciplinary approach.